Inventing Tradition: Webern's Piano Variations in Early Recordings. (15th June 2017) - Cook, Nicholas
ABSTRACT: Webern's Piano Variations Op. 27 were first performed two years before the outbreak of the Second World War, but it was only after the war – and in very different aesthetic and ideological circumstances – that a performance tradition developed. Through a combination of computer‐assisted close reading and contextual analysis of the first movement, this article traces the competing stylistic and ideological directions of early performances – one deriving from the pre‐war tradition of the Schoenberg circle, the other from the European avant‐garde associated with Darmstadt and Die Reihe – and the processes of negotiation through which a more or less consensus interpretation emerged around the end of the 1960s. My aims are to explore ways in which empirical approaches can be deployed for musicological purposes, to relate recorded performances to their historical contexts and to link the story of Op. 27 to the development of music‐theoretical approaches that see performance as a function of compositional structure. Key recordings on which the article is based are presented online as Sonic Visualiser session files coordinated with the text.